Esterification of Fatty Acids in Greases to Fatty Acid Methyl Esters with Highly Active Diphenylamine Salts. (20th January 2013) - Ngo, Helen L.; Vanselous, Heather; Strahan, Gary D.; Haas, Michael
Abstract: Diphenylamine sulfate (DPAS) and diphenylamine hydrochloride (DPACl) salts were found to be highly active catalysts for esterification and substantial transesterification of inexpensive greases to fatty acid methyl esters (FAME). In the presence of catalytic amounts of DPAS or DPACl and excess methanol, the free fatty acids as well as the acylglycerols in waste greases were converted to FAME at 125 °C within 1 h. Although the DPAS and DPACl catalysts were found to have similar catalytic activities to their parent liquid acids (i.e., sulfuric and hydrochloric acids) the diphenylammonium salts are much easier to work with than concentrated liquid acids.